Continued play following sport-related concussion in United States youth soccer - Zynda, A. J.; Sabatino, M. J.; Ellis Jr., H. B.; Miller, S. M. (International Journal of Exercise Science, 2020)
Medical guidelines and legislation in the US call for immediate removal from play and prohibit continued play on the same day if a concussion is suspected. However, there is limited literature examining whether these guidelines and laws are being followed in youth soccer. The purpose of this study was to identify the frequency at which youth soccer players continued play on the same day following sport-related concussion and factors that may be associated with this behavior. A retrospective review of youth soccer players diagnosed at the initial clinic visit with a sport-related concussion was performed. Participants were categorized into groups, those who continued play on the same day as their concussion (PLAY) and those who did not (NO PLAY). Records were reviewed for demographics, injury characteristics, SCAT3™ symptoms, mBESS and ImPACT® results, symptom resolution and return to play protocol initiation. Fifty-eight girls (mean age: 14 years, range: 7-18 years) and 29 boys (mean age: 14.4 years, range: 6-18 years) participated in this study. Thirty of 58 girls (51.7%) continued play the same day compared to only 5 of 29 boys (17.2%; p=0.002). The odds of continued play in girls were 5 times as high as the odds of continued play in boys (OR=5.05; 95% CI, 1.59-19.3). Overall, 35 (40.2%) soccer players continued play on the same day following a concussion. In conclusion, approximately 40% of youth soccer players continued play on the same day as their concussion. Girl soccer players demonstrated a significantly higher frequency of continued play than boys.